ULTRASOUND MARKERS OF PREMANIFEST ATHEROSCLEROSIS OF CAROTID AND FEMORAL ARTERIES IN ASSESSMENT OF CARDIOVASCULAR RISK - A. I. Ershova; S. A. Boytsov; О. M. Drapkina; Т. V. Balakhonova (Российский кардиологический журнал, 2018)
More than a half of cardiovascular events occur in low to moderate cardiovascular risk patients if assessed based on the traditional risk factors. At the same time, ultrasound examination of arteries makes it possible to reveal atherosclerosis even at early stages of its development. High prevalence of subclinical atherosclerosis in low to moderate risk patients, which is a realization of traditional and “unknown” risk factors, makes ultrasound examination a useful method for risk stratification. The review is focused on ultrasound markers of atherosclerosis with association to traditional risk factors, on the possibility to improve predictive role of current scores and influence on outcomes. Predictive significance of the markers is regarded for primary prevention in general population, in high risk persons and from the perspective of quantitative indicator of atherosclerotic lesion grade or plausibility as a surrogate cardiovascular diseases marker.